Perancangan Sistem Informasi Pemesanan Kamar Hotel Berbasis Web di Hotel Borobudur Jakarta - Ni Ketut, Narindra Ayuning Pradewi; Sujatha, Drs. Dewa Ketut (Program Studi Administrasi Perhotelan, 2024)
The five-star Hotel Borobudur Jakarta, located in the heart of Jakarta, has been thepreferred choice for travelers for decades. However, challenges in an unoptimized roomreservation system pose constraints. The need for an ef icient online booking system becomesmore pressing with technological advancements. The hotel, with 695 rooms, hasn't fullyleveraged the internet for quick and ef icient reservations.This research focuses on designing a web-based room reservation system using theData Flow Diagram (DFD) method. The approach aims to understand the hotel's needs inenhancing the reservation process. Applying DFD principles, the study designs a system forbetter accessibility, enabling potential guests to easily book rooms. The system aims tosimplify guest experiences and assist hotel management in monitoring and managingreservations ef ectively. The success of implementing this web-based room reservation systemat Hotel Borobudur Jakarta is expected to enhance guest services and overall operationalef iciency. With a structured, technology-based approach, the system is anticipated to be theright solution for the hotel's room reservation challenges.